Application of Yoga in the Treatment of Chronic Headaches - Hanna Barska-Kobylińska; Martyna Byrska; Marta Janura; Maja Weimann; Grzegorz Przywara; Oliwia Biegańska; Emilia Biczak; Ewa Katarzyna Malaka; Marlena Zubiak; Sara Langner (Quality in Sport)
Introduction Headaches represent a significant public health problem, ranking sixth among the most common causes of disability worldwide. They negatively affect the quality of life, particularly during the working years, leading to high economic costs. Despite their widespread prevalence, headaches are often underdiagnosed and inadequately treated, which exacerbates their negative impact on society.